The Specific Features of the Systemic History of the International Relations and World Politics - I. V. Kolosova (Проблемы постсоветского пространства)
The article considers the specific features of the systemic approach to the history of the international relations and world politics. International relations are viewed as a single complex organism, which is greater than the sum of its parts. The freedom of actions of the states is limited by the frames of the system of international relations, the part of which they are. Each system has its spatial and temporal characteristics. In the period of the Early Modern Age the process of formation of the national states unrolls. In the XVII century The Thirty Years’ War became the largest event of the international life, at the end of which the Westphalian system of the international relations was born. In the XIX century after the victory over Napoleon the Vienna system of international relations develops. Both Westphalian and Vienna systems are European regional systems. The end of the World War I war resulted in formation of the Versailles-Washington world order, which was the first attempt to build the global system of the international relations. After the victory of the anti-Hitler coalition in the World War II the global bipolar Yalta-Potsdam system was built, which existed till the dissolution of the USSR. At the present moment the new system of international relation is developing, with polycentrism and diversity of actors as its’ specific features.